Building Buying Interest In The Digital Era: The Role Of Influencers, Promotional Content And MJB Beauty's Brand Image - Alysa Noer Aida; Sundari Rahman; Andi Muhammad Irwan; Musmulyadi (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
This study examines the influence of influencers, promotional content, and brands on the buying interest of MJB Beauty, a local cosmetics brand in Indonesia. The problem studied is the inconsistency of the influence of digital marketing strategies on consumer buying interest, especially in beauty products. The purpose of the study was to analyze the partial and simultaneous influence of influencers, promotional content, and brands on buying interest. This study used a quantitative method with a multiple linear regression approach, involving 100 respondents who were Instagram followers of influencer MJB Beauty. Data were analyzed using SPSS version 25. The results showed that influencers and promotional content partially had a positive and significant effect on buying interest, with t-calculated values of 5,533 (p=0.000) and 5,956 (p=0.001), respectively. However, brands did not have a significant effect partially (t-count=0.630, p=0.530). Simultaneously, the three variables had a positive and significant effect (F-count=108.491, p=0.001) with a contribution of 77.2% to buying interest. The study concluded that marketing strategies involving influencers and engaging promotional content are highly effective, but MJB Beauty needs to strengthen its brand identity to increase buying interest.